2012
DOI: 10.1111/jfbc.12004
|View full text |Cite
|
Sign up to set email alerts
|

Growth Medium Optimization for Biomass Production of a Probiotic Bacterium,Lactobacillus rhamnosus ATCC 7469

Abstract: This study was undertaken to determine the glucose, yeast extract, tryptone and Tween 80 concentrations in a cultivation medium for optimal biomass production of a probiotic bacterium, Lactobacillus rhamnosus ATCC 7469. Using response surface methodology, a central composite rotatable design was applied to allocate treatment combinations. A polynomial regression model containing linear, quadratic, cubic and quartic terms was used for analysis of the experimental data. Effects involving all four factors evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
0
2
1
2
Order By: Relevance
“…0.95% (w/v) for each, were slightly higher than the level of supplementation reported by Masuda et al, (2006). On the other hand, the level optimized for different media constituents in the present study are found to be less than the data reported by other researchers (Liew et al, 2005;Bevilacqua et al, 2008;Chang and Liew, 2012). The difference found in the studies regarding level of YE and PP to obtain maximum biomass production from lactobacilli may be mainly due to addition of other ingredients such as glucose, meat extract, tryptone, casein or other protein hydrolysates and salts along with YE and PP which may provide growth nutrients to lactobacilli and thereby reduces the requirement of YE and PP.…”
Section: Effect On Biomasscontrasting
confidence: 56%
“…0.95% (w/v) for each, were slightly higher than the level of supplementation reported by Masuda et al, (2006). On the other hand, the level optimized for different media constituents in the present study are found to be less than the data reported by other researchers (Liew et al, 2005;Bevilacqua et al, 2008;Chang and Liew, 2012). The difference found in the studies regarding level of YE and PP to obtain maximum biomass production from lactobacilli may be mainly due to addition of other ingredients such as glucose, meat extract, tryptone, casein or other protein hydrolysates and salts along with YE and PP which may provide growth nutrients to lactobacilli and thereby reduces the requirement of YE and PP.…”
Section: Effect On Biomasscontrasting
confidence: 56%
“…The method enables to obtain a large amount of data from a reduced number of experiments and to study the influence of different input variables on a specific response, including the interactions between the studied factors. RSM has been successfully used for the optimization of culture media for different microorganisms including lactobacillus species [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotic lactobacilli are nutritionally fastidious organisms. Therefore, their viability and growth activity are commonly influenced by growth factors such as medium formulations, pH, temperature, and others (Chang & Liew 2013;Terpou et al 2017;Dang et al 2021). The less cell mass production of lactic acid bacteria during its industrial production using a bioreactor is attributed to the reduced growth rate of cells and high production of lactate (Du Toit et al 2013).…”
Section: Challenges Regarding the High Yield Of Biomass Of Probioticsmentioning
confidence: 99%